Communicating Health Uncertainty: How Australia's only National Broadsheet Newspaper Reported the Emerging COVID-19 Pandemic. (June 2021) - Furlan, Patrizia
The news media play an important role in communicating health topics to the public (Hallin & Briggs, 2015, Media, Culture & Society, vol. 37, pp. 85–100). Often journalists are the first to raise the alarm about the safety of vaccines, medicines and pathogen outbreaks including emerging infectious diseases (Joffe, 2011, Public Understanding of Science, vol. 20, pp. 446–460). But the news media have also been accused of distorting, exaggerating or amplifying risks which can lead to fear-mongering and public panic (Klemm et al., 2016). This paper examines how the only national broadsheet newspaper of Australia, The Australian, reported the COVID-19 pandemic from its first media appearance in January 2020 with a focus also on 2 days in February and March 2020. These timeframes coincided with significant coronavirus milestones for Australia, such as the first COVID-19 infection; the first deaths; and the World Health Organisation's declaration of a global pandemic. This paper found that The Australian coverage was not hyped but measured, with heavy reliance on analysis of the economic fallout of COVID-19. It also found evidence the conservative newspaper used war metaphors to convey the fight against the coronavirus.